2009
DOI: 10.1017/s1742170508002470
|View full text |Cite
|
Sign up to set email alerts
|

Organic broccoli production on transition soils: Comparing cover crops, tillage and sidedress N

Abstract: Little information is available about how farmers in transition to organic practices should manage short-and long-term N fertility. The objectives of this research were (1) to evaluate the leguminous cover crops lablab (Dolichos lablab L.), soybean (Glycine max L.), sunn hemp (Crotalaria juncea L.) and a mixture of sunn hemp and cowpea (Vigna sinensis Endl.) as N sources; (2) to compare N availability and broccoli yield when cover crops were incorporated with conventional tillage (CT) or retained as a surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…as a cover crop for fall broccoli in Oklahoma was not recommended as a result of N tie-up by cowpea residues and a tendency of increased mortality of broccoli transplants in cowpea plots. In a transition field in Vermont, Schellenberg et al (2009) found that broccoli yield was unaffected by various leguminous cover crop applications and a moderate rate of in-season N was recommended. N immobilization could be avoided by incorporating the cover crop at an earlier growth stage when the C:N ratio is lower (Diniz et al, 2007); however, this may not always be an option for growers, especially in central coastal California because spring rains and wet soil conditions can prohibit this practice.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…as a cover crop for fall broccoli in Oklahoma was not recommended as a result of N tie-up by cowpea residues and a tendency of increased mortality of broccoli transplants in cowpea plots. In a transition field in Vermont, Schellenberg et al (2009) found that broccoli yield was unaffected by various leguminous cover crop applications and a moderate rate of in-season N was recommended. N immobilization could be avoided by incorporating the cover crop at an earlier growth stage when the C:N ratio is lower (Diniz et al, 2007); however, this may not always be an option for growers, especially in central coastal California because spring rains and wet soil conditions can prohibit this practice.…”
Section: Resultsmentioning
confidence: 98%
“…Work has shown that the rate of mineralization of available N from a low C:N (less than 20) cover crop typically increases over a 3-to 6-week period after incorporation and then returns to pre-incorporation levels by Week 6 to 8 in this region, the central coast of California (Gaskell, 2004). Therefore, a cover crop can be a valuable source of short-term N but longer season vegetable crops after a cover crop rotation may require supplemental applications of fertilizer N to supply late-season N (Delate et al, 2008;Schellenberg et al, 2009;Schonbeck et al, 1993;Scow et al, 1994;Smith, 1992;Temple et al, 1994).…”
mentioning
confidence: 99%
“…This would indicate that N may not have been limiting for NT and ST treatments in this study. However, because leaf N measurements were taken at only one point in time (7-8 weeks after planting), it is possible that plants in NT and ST treatments experienced N deficiency early in the 2014 season (Schellenberg et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found that NT treatments yielded as much or more than CT in production of tomatoes (Creamer et al, 1996a;Delate et al, 2012), bell pepper (Delate et al, 2008), spinach (Lounsbury and Weil, 2015), and onion (Vollmer et al, 2010), while others found that NT treatments yielded poorly (Díaz-P erez et al, 2008;Leavitt et al, 2011). Schellenberg et al (2009) found that an NT system using flail mowed warmseason legume cover crops [lablab (Dolichos lablab L.), soybean (Glycine max L.), sunn hemp (Crotalaria juncea L.), and a mixture of sunn hemp and cowpea (Vigna sinensis Endl.)] had similar yields for spring broccoli, but reduced yields for fall broccoli, compared with CT.…”
mentioning
confidence: 99%
“…Similarly, hairy vetch was determined to be the best cover crop for no-till tomato production without compromising yield (Abdul-Baki et al 1996). Schellenberg et al (2009) found that a no-tillage system using flail mowed warm-season legume cover crops Egyptian bean, soybean, sunn hemp, and a mixture of sunn hemp and cowpea had similar yields for spring broccoli (Brassica oleracea L. var. italic), but reduced yields for fall broccoli, compared with conventional tillage.…”
Section: Reduced Tillagementioning
confidence: 99%